2018
DOI: 10.5935/0946-5448.20180009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adding Lidocaine to Dexamethasone in the Intra-tympanic Injection for Management of Tinnitus: A Prospective, Randomized, Controlled Double-blinded Trial

Abstract: ITLD seems to be effective for SIT than ITD alone. The indication of ITLD for tinnitus needs to be limited to specific cases of resistant medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Savastano [30] Prospective clinical trial Significant improvement in level of disturbance and tinnitus loudness was observed O'Brien et al [31] Pilot, prospective efficacy trial Significant improvement on the tinnitus functional index scores in participants Elzayat et al [32] Prospective, randomized, controlled double-blinded study The effectiveness rates were 74.5% in the intratympanic lidocaine+dexamethasone group, and 50.0%, 50.5%, and 40.0% in dexamethasone alone group 은행잎 추출제…”
Section: Study Study Design Resultsmentioning
confidence: 99%
“…Savastano [30] Prospective clinical trial Significant improvement in level of disturbance and tinnitus loudness was observed O'Brien et al [31] Pilot, prospective efficacy trial Significant improvement on the tinnitus functional index scores in participants Elzayat et al [32] Prospective, randomized, controlled double-blinded study The effectiveness rates were 74.5% in the intratympanic lidocaine+dexamethasone group, and 50.0%, 50.5%, and 40.0% in dexamethasone alone group 은행잎 추출제…”
Section: Study Study Design Resultsmentioning
confidence: 99%
“…Over six months, these forty-four patients were assessed for tinnitus, and at the end of six months period, a significant and appreciable relief in tinnitus was found in patients treated with the combination of Dexame-thasone and Lidocaine as compared to dexamethasone alone. 19…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic agents applied in the treatment of hearing loss include glutamate inhibitors such as caroverine (Tinnex), derivatives of trimetazidine anti-ischemic agent such as trimetazidine dihydrochloride (Adexor), and lidocaine perfusion of the inner ear specifically for tinnitus. These treatments are not available in all countries and reports of effectiveness are controversial [ 56 , 57 , 58 ].…”
Section: Current Treatment Methodsmentioning
confidence: 99%